De la investigación formativa a la investigación científica : huellas del proceso (2010)
ABSTRACT: To the current curriculum of the Social Work program of the Universidad de Antioquia is relevant to execute academic processes that articulate formative research and scientific research, contributing from the academic, to explanatory productions of the social conditions to endeavor to improve them. The purpose on this reflection here is, on the one hand, to report the sense of assuming as a transversal axis the research for the Social Work program; and on the other hand, to illustrate its importance and the need to execute actions that make it possible and boost it. To report these aspects leads to focus the attention on the research senses: scientific and formative, and on its connections. Moving from the speech to the action generates the visualization of plausible ways to conjugate formative research with a clear scientific projection. The traces experienced from the research: Planning as an option for development: Contemporary bet. Study case of Local Planning and Participative Budget program, 2004-2007, “Comuna 1”, Municipality of Medellín, executed under the frame of a formative research process by eleven students from the Social Work program of Universidad de Antioquia, becomes a way to verify that it is possible to simultaneously articulate scientific and formative aspects. To reflect on this topic proposed here is significant in curriculum meanings, because it tries the theoretical and methodological consolidation of the Research Group of Social Intervention (GIIS). In this sense, it is expected that its content motivates to students and professors, to start of inspiring processes of an investigative spirit.